Hyperglycemia in the Perioperative Period of Liver Transplantation: A Scoping Review - Lima, Manuela Izidio de; Cavalcanti Filho , Djalma da Silva; Silva, Gabriel Henrique Gomes e; Silva, José Henrique da; Ferreira, José Vitor Lins; Freire, Marcelo Irineu de Moura; Almeida, Rafael Eduardo Correntesa de; Macedo, Victor Presto de Oliveira; Silva, Hugo Rafael de Souza e; Fonseca Neto, Olival Cirilo Lucena da (Brazilian Journal of Transplantation, 2025)
Objective: To find evidence on the influence of hyperglycaemia in the perioperative period of liver transplantation. Methodology: This is a scoping review of the PubMed, VHL and Web Of Science databases. The following descriptors were used: ‘Liver transplantation’, ‘Hyperglycemia’ and ‘Blood Sugar Control’ with the Boolean operator ‘AND’, and articles of relevance to the topic were selected. Initially, 139 articles were selected, all published in the last 20 years, in Portuguese and English. After analysis, 10 articles corresponded to the proposed objective. Results: In the comparison between strict control and conventional glucose control in patients undergoing liver transplantation, the average intraoperative glycaemia was 143.3 mg/dL in the conventional group and 130.7 mg/dL in the strict control group, which received more insulin. The intensive care unit stay was similar with a mean of 3 days, but survival improved significantly with mean intraoperative glycaemia ≤120 mg/dL. Patients with post reperfusion syndrome required insulin infusion more often. New-onset diabetes mellitus and early bacteraemia were more frequent in the post-reperfusion syndrome group. AST and ALT levels were higher in hyperglycaemic patients. Surgical site infection rates correlated with postoperative hyperglycaemia, with 20% for glycaemia <200 mg/dL and 52% for glycaemia ≥200 mg/dL. Patients with postoperative glucose <200 mg/dL had a lower rejection rate compared to those with glucose ≥200 mg/dL. Diabetics had higher preoperative glycaemia than non-diabetics, with a gradual reduction after liver transplantation, while non-diabetics had a peak on days 2 and 3 before returning to baseline levels. High glucose levels 48-72 hours post-transplant were associated with higher mortality and a worse response to insulin treatment in the first week. Conclusion: Strict glycaemic control in patients undergoing liver transplantation resulted in lower intraoperative glycaemia and significantly better survival for those with glycaemia ≤120 mg/dL, as well as lower rates of infection, rejection and mortality, especially in non-diabetics.